Promoting Fundamental Movement Skills and Physical Literacy Among 8–12-Year-Old Children: Feasibility Insights from an 8-Week Pilot Program in Southwestern Ontario - Danielle Salters; Emily Chauvin; Sarah J. Woodruff; Sara M. Scharoun Benson (Children)
Background/Objectives: Global levels of physical activity are in decline, accompanied by low levels of competence in fundamental movement skills (FMSs) required to meaningfully participate in lifelong physical activity. This study aimed to explore the effects of an 8-week pilot program on the development of FMSs for children in a lower socioeconomic area through a game-based physical activity approach. Methods: Children (N = 30) were recruited from a lower socioeconomic area to participate in a community-offered PA program. This 8-week pilot program focused on game-based intervention, with weekly 1.5 h sessions to promote active play and development of FMSs. Each session was structured to ensure at least one FMS based on the Test of Gross Motor Development—Third Edition (TGMD-3) was emphasized to promote practice in these skills. The TGMD-3 was employed as a pre- and post-test measure of motor competence. Results: Children who completed both the pre- and post-test assessments (N = 11) demonstrated improvements in both locomotor (p = 0.166) and ball skill (p = 0.184) scores, though these were not significant. Additional analyses at baseline with all participants (N = 22; 8 not present at baseline testing) were insignificant, but descriptive statistics demonstrated that boys scored higher in ball skill scores, while girls scored higher in locomotor skill scores. Older children at baseline were found to score significantly higher than younger children in ball skill scores. Conclusion: The results highlighted that the game-based intervention did demonstrate some improvements for FMSs, highlighting a need for further development of the program and the participation of more children for more strongly powered analysis and to account for program withdrawal or dropout.